2014
DOI: 10.1021/jo500446f
|View full text |Cite
|
Sign up to set email alerts
|

Natural Tetraponerines: A General Synthesis and Antiproliferative Activity

Abstract: ABSTRACT:A stereocontrolled general methodology to access all natural tetraponerines from (+)−T1 to (+)−T8 is detailed. Two consecutive indium-mediated aminoallylations with the appropriate enantiomer of chiral N-tert-butylsulfinamide and a thermodynamic control at the aminal stereocenter, allow the formation of each natural tetraponerine with excellent stereoselectivity. The use of 4-bromobutanal in the first aminoallylation leads to the formation of 5-6-5 tetraponerines whilst 5-bromopentanal is required to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 37 publications
3
38
1
Order By: Relevance
“…Studies into the venom of Tetraponera ants revealed a unique class of neurotoxic bioactive compounds termed tetraponerines. Tetraponerines are tricyclic alkaloids isolated for the first time in 1987 from venom of the New Guinean pseudomyrmecine ant 60 . These molecules, designated T1 – T8 ( 12 – 15 , Fig.…”
Section: Hymenoptera (Bees Wasps Ants and Sawflies)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies into the venom of Tetraponera ants revealed a unique class of neurotoxic bioactive compounds termed tetraponerines. Tetraponerines are tricyclic alkaloids isolated for the first time in 1987 from venom of the New Guinean pseudomyrmecine ant 60 . These molecules, designated T1 – T8 ( 12 – 15 , Fig.…”
Section: Hymenoptera (Bees Wasps Ants and Sawflies)mentioning
confidence: 99%
“…The natural application of tetraponerines as neurotoxic agents led to interest in their cytotoxic profiles. An evaluation of the anti-proliferative activity of T5 – T8 against 4 different carcinoma cell lines highlighted the importance of C5 configuration on potency 60 . Furthermore, T7 exhibited an impressive cytotoxic profile on the breast carcinoma cell line MCF-7.…”
Section: Hymenoptera (Bees Wasps Ants and Sawflies)mentioning
confidence: 99%
“…By contrast, five-membered ring formation by displacement of a halide leaving group is far more usual and has been implemented in several ways (Scheme 2). It has been accomplished either at 50°C by treatment with KOH in H 2 O/THF [17] or tBuOK in iPrOH, [13] or at room temperature in THF using LiHMDS [18] (see the formation of 6), KHMDS, [19] or a combination of NaH and a crown ether additive (15-Crown-5). [20] As illustrated with 7, the latter conditions are tolerant of functionalized substrates.…”
Section: Reactions Involving Metallated N-tert-butanesulfinamides As mentioning
confidence: 99%
“…Other examples of cross metatheses where one of the partners is simple and readily available include: (1) ethylene with 1,4-butadiene polymers (depolymerization) [481], and with trans 1,4-polyisoprene (also using 1-octene as well as ethylene) [482]; (2) [486], with an allylated pyrroloindoline system for norcardioazine A and B total synthesis [487], and with an allylated flavonoid derivative for total synthesis of poinsettifolin A [488]; (4) cis 3-hexene with an allyltetrahydroquinoline system for total synthesis of angustureine (including many examples of RCM to form six-membered ring α,β-unsaturated lactams) [489], and with a homoallylamine derivative for synthesis of tetraponerines [490]; (5) various 1-alkene derivatives and vinylated seven-membered ring aminosugars [491];…”
Section: )mentioning
confidence: 99%